Alpha centauri - Siegel, Robert, 1939-2012.; Mitchell, Kurt. (Westchester, Ill. : Cornerstone Books, 1980)
While visiting a farm in England, Becky is carried back through time to ancient Britain where ruthless men are seeking to exterminate a race of benevolent centaurs.
Keywords: Centaurs -- Fiction; Time travel -- Fiction